Responses of two Acacia species to drought suggest different water-use strategies, reflecting their topographic distribution - Uni, Daphna; Sheffer, Efrat; Klein, Tamir; Shem-Tov, Rachamim; Segev, Nitzan; Winters, Gidon (Frontiers in Plant Science, 2023)
Introduction Soil water availability is a key factor in the growth of trees. In arid deserts, tree growth is limited by very dry soil and atmosphere conditions. Acacia tree species are distributed in the most arid deserts of the globe, therefore they are well adapted to heat and long droughts. Understanding why some plants do better than others in some environments is a key question in plant science. Methods Here we conducted a greenhouse experiment to continuously and simultaneously track the whole-plant water-balance of two desert Acacia species, in order to unravel their physiological responses to low water availability. Results We found that even under volumetric water content (VWC) of 5-9% in the soil, both species maintained 25% of the control plants, with a peak of canopy activity at noon. Moreover, plants exposed to the low water availability treatment continued growing in this period. A. tortilis applied a more opportunistic strategy than A. raddiana, and showed stomatal responses at a lower VWC (9.8% vs. 13.1%, t4= -4.23, p = 0.006), 2.2-fold higher growth, and faster recovery from drought stress. Discussion Although the experiment was done in milder VPD (~3 kPa) compared to the natural conditions in the field (~5 kPa), the different physiological responses to drought between the two species might explain their different topographic distributions. A. tortilis is more abundant in elevated locations with larger fluctuations in water availability while A. raddiana is more abundant in the main channels with higher and less fluctuating water availability. This work shows a unique and non-trivial water-spending strategy in two Acacia species adapted to hyper-arid conditions.